Beslutsstödsystem för arméns logistik - Rosenqvist,Axel (2025)
The significantly altered global security environment and the changing operational context in which the Swedish Army is expected to act place increasing demands on the availability of the Army’s technical systems. One possible solution to facilitate the planning and execution of maintenance is the use of digital decision support systems. This study explores which functionalities should be included in a decision support system tailored to the technical services of the Swedish Army. It further discusses how these functionalities can be implemented and which development methodology is most suitable for creating such a system. The work was carried out by developing a prototype of a decision support system, which then served as the basis for discussions within a focus group. An iterative approach was adopted throughout the process, in line with the methodology of design science research. The study defines the Swedish Army’s organization and logistics concept up to brigade level and discusses the wide range of functionalities that such systems may provide, as well as how these functionalities can be further developed. Finally, the study concludes that the greatest limitation for developing systems adapted for predictive maintenance lies in the insufficient availability of high–quality data, and that system development must take place in close collaboration with end–users. The latter is essential to ensure that the system produces outcomes that are relevant and useful for the intended users.
Keywords: Decision support systems; predictive maintenance; military software development; machine learning; beslutsstödsystem; prediktivt underhåll; militär mjukvaruutveckling; Maskininlärning